Medullary Endocannabinoids Contribute to the Differential Resting Baroreflex Sensitivity in Rats with Altered Brain Renin-Angiotensin System Expression - Schaich, Chris L.; Grabenauer, Megan; Thomas, Brian F.; Shaltout, Hossam A.; Gallagher, Patricia E.; Howlett, Allyn C.; Diz, Debra I. (Frontiers in Physiology, 2016)
CB1 cannabinoid receptors are expressed on vagal afferent fibers and neurons within the solitary tract nucleus (NTS), providing anatomical evidence for their role in arterial baroreflex modulation. To better understand the relationship between the brain renin-angiotensin system (RAS) and endocannabinoid expression within the NTS, we measured dorsal medullary endocannabinoid tissue content and the effects of CB1 receptor blockade at this brain site on cardiac baroreflex sensitivity (BRS) in ASrAOGEN rats with low glial angiotensinogen, normal Sprague-Dawley rats and (mRen2)27 rats with upregulated brain RAS expression. Mass spectrometry revealed higher levels of the endocannabinoid 2-arachidonoylglycerol in (mRen2)27 compared to ASrAOGEN rats (2.70±0.28 vs. 1.17±0.09 ng/mg tissue; P < 0.01), while Sprague-Dawley rats had intermediate content (1.85 ± 0.27 ng/mg tissue). Microinjection of the CB1 receptor antagonist SR141716A (36 pmol) into the NTS did not change cardiac BRS in anesthetized Sprague-Dawley rats (1.04±0.05 ms/mmHg baseline vs. 1.17±0.11 ms/mmHg after 10 min). However, SR141716A in (mRen2)27 rats dose-dependently improved BRS in this strain: 0.36 pmol of SR141716A increased BRS from 0.43±0.03 to 0.71±0.04 ms/mmHg (P < 0.001), and 36 pmol of SR141716A increased BRS from 0.47±0.02 to 0.94±0.10 ms/mmHg (P < 0.01). In contrast, 0.36 pmol (1.50±0.12 versus 0.86±0.08 ms/mmHg; P < 0.05) and 36 pmol (1.38±0.16 versus 0.46±0.003 ms/mmHg; P < 0.01) of SR141716A significantly reduced BRS in ASrAOGEN rats. These observations reveal differential dose-related effects of the brain endocannabinoid system that influence cardiovagal BRS in animals with genetic alterations in the brain RAS.